Distinguishing adrenal cortical carcinomas and adenomas: a study of clinicopathological features and biomarkers. Issue 4 (23rd November 2013) - Wang, Cuiping; Sun, Yang; Wu, Huanwen; Zhao, Dachun; Chen, Jie
<x xml:space="preserve">Abstract</x> Aims To determine clinicopathological criteria and molecular markers helpful in distinguishing adrenocortical carcinomas (ACCs) from adrenocortical adenomas (ACAs). Methods and results We analysed retrospectively the clinical and pathological features of 50 adrenal cortical tumours, and tested the expression of miR483‐3p by in‐situ hybridization as well as the expression of IGF2 and Smad4 by immunohistochemistry. We found that tumour size, tumour weight, hormonal function and the Weiss system are all high‐efficacy criteria for differentiating malignant from benign tumours (P < 0.001). MiR483‐3p was overexpressed in 68% (17 of 25) of ACCs compared to 12% (three of 25) of ACAs (P < 0.05). Using a combination of miR483‐3p and Smad4 improved diagnostic accuracy. Molecular markers were then tested in an independent set of 15 borderline tumours. We confirmed that the combined use of miR483‐3p and Smad4 immunochemistry can complement the Weiss score in the diagnosis of ACC in cases that display borderline histology. Conclusions Tumour size, tumour weight, hormonal function and the Weiss system are useful clinicopathological criteria that can result in accurate diagnosis of most ACCs and ACAs. In challenging cases, miR483‐3p and Smad4 expression may help in distinguishing these two entities.